Thomas Hylland Eriksen a Marek Jakoubek (eds): Ethnic Groups and Boundaries Today. A Legacy of Fifty Years - Maher, Vanessa (Lidé města, 2023)
A review of the book by Thomas Hylland Eriksen and Marek Jakoubek.